Domestic Negotiations : Gender, Nation, and Self-Fashioning in US Mexicana and Chicana Literature and Art - McMahon, Marci R., 1975- (Book collections on Project MUSE., 2013)
This book explores how U.S. Mexicana and Chicana authors and artists across different historical periods and regions, and how they use domestic space to actively claim their own histories. Drawing from a range of archival sources and cultural productions, the book demonstrates how the very sites of domesticity are used to engage with the many political and recurring debates about race, gender, and immigration affecting the lives of Mexicanas and Chicanas from the early twentieth century up through the twenty-first century.